Pengaruh Profitabilitas, Growth, Size, dan HPM terhadap Net Profit Margin Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia (BEI) - Herman Herman; Estralita Trisnawati; Verawati Verawati (Politeknik Ganesha Medan, 2023)
This study aims to measure the effect of profitability through the ratio of ROA (Return on Assets) and ROE (Return on Equity), company growth, company size and HPM (Mineral Benchmark Price) on Profit Margins of mining companies, especially nickel that listed on the Indonesia Stock Exchange (IDX). The research conducted is a quantitative study and the subjects in this study are all mining sector companies listed on the Indonesia Stock Exchange (IDX) in the 2020-2022 period. The data used is secondary data and were obtained through the official website of the Indonesia Stock Exchange (IDX) in the form of annual financial reports. The sample selection used purposive sampling method. Testing the data in this study used the Statistical Package for the Science 25 (SPSS 25). There were 66 samples selected using the purposive sampling method, so the criteria in this study were as follows: sample selection criteria and for companies that have been registered since 2010 and have complete financial report data from 2020-2022. The results of this study are as follows: Profitability (ROA) has a positive and significant effect on company NPM, Profitability (ROE) has a negative and significant effect on company NPM, and HPM have a positive and significant effect on company NPM. Whereas growth and size not have a significant effect on company NPM.